The Influence Of Servant Leadership, Entrepreneurial Mindset, Entrepreneurial Climate, Knowledge Management And Organizational Development On Performance At Private Higher Education In The LLDikti III - Friska Intan Sundari (Journal Economic Excellence Ibnu Sina, 2023)
This study aims to identify the influence of Servant Leadership, Entrepreneurial Mindset, Entrepreneurial Climate, Knowledge Management and Organizational Development on Performance at Private Higher Education in the LLDikti III region. This study uses quantitative, in this research method is a survey method, which is obtained from the results of collection using a questionnaire. The population in this study were lecturers from private universities in the LLDikti III area. The sample in this study were 376 respondents. The analysis tool used is SmartPLS 3 with SEM (Sctructual Equation Modeling) based on PLS (Partial Least Square). The results of this study state that SL influences EM, SL influences EC, SL influences KM, SL influences OD, EM influences EC, EC influences KM, KM influences OD, SL influences college performance, EM influences college performance, EC influences college performance , KM does not affect college performance and OD does not affect college performance.